An evidence-based guide to the treatment of osteonecrosis of the femoral head. (October 2017) - Chughtai, M.; Piuzzi, N. S.; Khlopas, A.; Jones, L. C.; Goodman, S. B.; Mont, M. A.
Abstract : Non-traumatic osteonecrosis of the femoral head is a potentially devastating condition, the prevalence of which is increasing. Many joint-preserving forms of treatment, both medical and surgical, have been developed in an attempt to slow or reverse its progression, as it usually affects young patients. However, it is important to evaluate the best evidence that is available for the many forms of treatment considering the variation in the demographics of the patients, the methodology and the outcomes in the studies that have been published, so that it can be used effectively. The purpose of this review, therefore, was to provide an up-to-date, evidence-based guide to the management, both non-operative and operative, of non-traumatic osteonecrosis of the femoral head. Cite this article: Bone Joint J 2017;99-B:1267–79.